2017
DOI: 10.1097/mcg.0000000000000887
|View full text |Cite
|
Sign up to set email alerts
|

EUS-guided Gastrojejunostomy Versus Laparoscopic Gastrojejunostomy

Abstract: Although the EUS-GJ group contained more complex patients, efficacy was similar between the groups. AEs were significantly lower in the EUS-GJ group. EUS-GJ is a safe and efficacious, minimally invasive option for patients with GOO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
184
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(198 citation statements)
references
References 12 publications
9
184
5
Order By: Relevance
“…Endoscopic ultrasound-guided gastroenterostomy (EUS-GE) with a lumen-apposing metal stent (LAMS) is a novel technique for palliative treatment of malignant GOO. It seems to combine the advantages of duodenal stenting and SGJ, while potentially overcoming their shortcomings [12][13][14][15][16]. EUS-GE is minimally invasive and shows fast relief of symptoms, possibly with lower stent failure and reintervention rates than duodenal stenting [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Endoscopic ultrasound-guided gastroenterostomy (EUS-GE) with a lumen-apposing metal stent (LAMS) is a novel technique for palliative treatment of malignant GOO. It seems to combine the advantages of duodenal stenting and SGJ, while potentially overcoming their shortcomings [12][13][14][15][16]. EUS-GE is minimally invasive and shows fast relief of symptoms, possibly with lower stent failure and reintervention rates than duodenal stenting [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…1 The development of walled-off necrosis (WON) is a late complication of acute severe necrotizing pancreatitis, and endoscopic necrosectomy (EN) has become an effective treatment for infected WON. A multicenter study [2][3][4] of EN in WON revealed clinical success rates from 75% to 91%. However, high mortality and morbidity rates of 6.7-11% and 14-33%, respectively, were found.…”
Section: Current Problems and Clinical Results Of Endoscopic Necrosecmentioning
confidence: 99%
“…As a new approach, endoscopic ultrasonography-guided gastrojejunostomy (EUS-GJ), which utilizes these advantages, has emerged in the clinical setting. [1][2][3][4] However, EUS-GJ is not always successful because of invisible jejunum under EUS due to air or collapse of the jejunum, leading to mispuncture to the large intestine and misdeployment of the stent. To overcome these problems, we developed the EUS-guided double-balloon-occluded gastrojejunostomy bypass (EPASS).…”
Section: Case Of Successful Endoscopic Ultrasonography-guided Gastrojmentioning
confidence: 99%
“…A recent international multicentre study that included 26 patients showed a technical and clinical success rate of 92 and 85%, respectively [73]. When compared to laparoscopic GJ, EUS-guided GJ seems to be associated with fewer adverse events and lower costs, as was described by a Spanish group in a comparative study [74]. Further studies comparing this approach with luminal stent placement are warranted.…”
Section: Eus-guided Gastrojejunostomymentioning
confidence: 94%